P102 Post-Hospitalisation Outpatient Pulmonary Rehabilitation: A Translational Gap?. (19th November 2012) - Jones, SE; Green, SA; Clark, AL; Dickson, MJ; Nolan, A-M; Moloney, C; Kon, SSC; Godden, J; Howe, C; Haselden, BM; Fleming, S; Man, WD-C
Abstract : Background: Recent trials and meta-analyses of early post-hospitalisation pulmonary rehabilitation (PR) in COPD have demonstrated improvements in exercise capacity, health-related quality of life and a reduction in hospital readmissions (Man et al., 2004; Seymour et al. 2010; Puhan et al. 2011). However anecdotal observation and evidence from recent trials suggest poor uptake of outpatient PR. The aim of the study was to map patient journeys to identify gaps or deficiencies in the referral pathway. Methods: All 224 patients discharged from Hillingdon Hospital following an acute exacerbation of COPD between November 2011 and May 2012 were included in the analysis. Referrals for post-exacerbation PR from Hillingdon Hospital were monitored during the same time period. A collaborative of 18 stakeholders from seven organisations across primary, secondary and community care services was convened and performed local process mapping. Structured telephone interviews were held with a convenience sample of 36 COPD patients who declined post-hospitalisation PR. Results: Despite excellent compliance with a COPD discharge bundle (95%), only 63 (28%) of the 224 discharges from Hillingdon Hospital were referred to the local PR provider. All referrals were offered initial assessment for PR within 2 weeks of discharge but 18 failed to attend on at least 2 occasions. A further 9 patients failed to start PR despite attending initial assessment. In total, only 36 (16%) patients out of all hospital discharges over a 6-month period started outpatient PR. The main reasons for patients declining outpatient PR were accessibility issues (40%), commitment to PR "too time-consuming" (20%) or "too unwell" (13%). Conclusion: Despite a strong evidence base, there is poor uptake of post-hospitalisation early PR. The majority of missed opportunities occur at the initial referral stage, although there is a significant drop-out even in those referred. Ongoing experience based design work will explore staff and patient attitudes that may influence referral and uptake rates.